Development and validation of an LC-MS/MS method for detection and quantification of in vivo derived metabolites of [Pyr(1)]apelin-13 in humans - Nyimanu, Duuamene (Sci Rep, 2019)
[Pyr(1)]apelin-13 is the predominant apelin peptide isoform in the human cardiovascular system and plasma. To date, few studies have investigated [Pyr(1)]apelin-13 metabolism in vivo in rats with no studies examining its stability in humans. We therefore aimed to develop an LC-MS/MS method for detection and quantification of intact [Pyr(1)]apelin-13 and have used this method to identify the metabolites generated in vivo in humans. [Pyr(1)]apelin-13 (135 nmol/min) was infused into six healthy human volunteers for 120 minutes and blood collected at time 0 and 120 minutes after infusion. Plasma was extracted in the presence of guanidine hydrochloride and analysed by LC-MS/MS. Here we report a highly sensitive, robust and reproducible method for quantification of intact [Pyr(1)]apelin-13 and its metabolites in human plasma. Using this method, we showed that the circulating concentration of intact peptide was 58.3 ± 10.5 ng/ml after 120 minutes infusion. We demonstrated for the first time that in humans, [Pyr(1)]apelin-13 was cleaved from both termini but the C-terminal was more susceptible to cleavage. Consequently, of the metabolites identified, [Pyr(1)]apelin-13((1–12)), [Pyr(1)]apelin-13((1–10)) and [Pyr(1)]apelin-13((1–6)) were the most abundant. These data suggest that apelin peptides designed for use as cardiovascular therapeutics, should include modifications that minimise C-terminal cleavage.